Revision of the Neotropical spider genus Acanthoctenus (Araneae: Ctenidae: Acanthocteninae) - Arizala, Stephany; Labarque, Facundo Martín; Polotow, Daniele (Zootaxa, 2021)
We revise the genus Acanthoctenus Keyserling, 1877 recognizing thirteen valid species, of which five are new species and two are re-validated. Further, we find one new synonymy and transfer one species. We describe Acanthoctenus alux sp. nov. from Guatemala, A. chickeringi sp. nov. and A. lamarrei sp. nov. from Panama, A. manauara sp. nov. from Brazil and A. torotoro sp. nov. from Bolivia. We revalidate Acanthoctenus dumicola Simon, 1906 stat. res. from Venezuela, and A. virginea (Kraus, 1955) stat. res., comb. nov. from El Salvador. We transfer Acanthoctenus mammifer to Viracucha mammifer (Mello-Leitão, 1939) comb. nov., from Brazil. Acanthoctenus maculatus Petrunkevitch, 1925 and Gephyroctenus kolosvaryi Caporiacco, 1947 are considered species inquirendae in Acanthocteninae and Ctenidae, respectively, and A. obauratus Simon, 1906 and A. rubrotaeniatus Mello-Leitão, 1947 are considered incertae sedis in Acanthocteninae and Acantheinae, respectively. We also describe for the first time the female of Acanthoctenus spiniger Keyserling, 1877, the type species of the genus. We provide illustrations of male and female diagnostic characters, genitalia, habitus, and measurements to support the genus re-description and further identification of its species. We yield a distributional map of the specimens recorded and the description of the natural history of Acanthoctenus manauara sp. nov.